High‐performance work system and employee performance: the mediating roles of social exchange and thriving and the moderating effect of employee proactive personality. (17th September 2018) - Zhang, Junwei; Bal, P Matthijs; Akhtar, Muhammad Naseer; Long, Lirong; Zhang, Yong; Ma, Zixiang
Abstract : Research on high‐performance work systems (HPWS) has drawn primarily from social exchange theory and human capital theory to unlock the underlying mechanisms in relation to employee performance. In addition to social exchange and human capital theory, a personal resources perspective can also be used to explain the effects of HPWS. In this cross‐level research, we examined the mediating roles of social exchange and thriving, and the moderating effect of proactive personality in the relationships between HPWS and task performance and organizational citizenship behavior (OCB) by analyzing a sample of 391 employees and 84 supervisors from 21 firms in China. Using multi‐level analyses, social exchange and thriving were found to mediate the effects of HPWS on employee task performance and OCB. Furthermore, proactive personality attenuated HPWS's direct effect on thriving and indirect effects on employee task performance and OCB through thriving. Finally, we discuss theoretical contributions, and practical implications of the study, as well as future research directions. Key points: High‐performance work system (HPWS) can enhance employee performance. The effects of HPWS manifest not only through social exchange but also by contributing to employees' personal resources. Employee proactive personality attenuates the effects of HPWS.